2020
DOI: 10.3892/etm.2020.8476
|View full text |Cite
|
Sign up to set email alerts
|

Effects of tenuifolin on rest/wake behaviour in zebrafish

Abstract: Insomnia is a common sleep disorder with a high prevalence and substantial adverse consequences. There is growing interest in identifying novel therapeutics from herbal medicine. Tenuifolin is a major constituent of the well-known anti-insomnia herb Radix Polygala. The present study investigated the neural activity in response to tenuifolin during rest/wake behaviour in zebrafish and identified the potential biological signalling pathways involved. An automatic video tracking system was used to monitor the beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
(51 reference statements)
0
4
0
Order By: Relevance
“…This might be due to the presence of Yuanzhi (Yuǎn zhì) and Shichangpu (Shí chāng pú) in the prescription. The traditional Chinese medicine Polygala has sleep-promoting, anti-inflammatory, and sedative effects, which may be achieved through the serotonergic system and the gamma-aminobutyric acid system [32]. Besides, Acori Tatarinowii Rhizoma (Shí chāng pú) is also a commonly used traditional Chinese medicine in the treatment of insomnia and epilepsy [33].…”
Section: Discussionmentioning
confidence: 99%
“…This might be due to the presence of Yuanzhi (Yuǎn zhì) and Shichangpu (Shí chāng pú) in the prescription. The traditional Chinese medicine Polygala has sleep-promoting, anti-inflammatory, and sedative effects, which may be achieved through the serotonergic system and the gamma-aminobutyric acid system [32]. Besides, Acori Tatarinowii Rhizoma (Shí chāng pú) is also a commonly used traditional Chinese medicine in the treatment of insomnia and epilepsy [33].…”
Section: Discussionmentioning
confidence: 99%
“…Afterward, the ingredients of 15 single herbs were analyzed by the same preparation method, liquid phase, and MS method as NLP. By comparing the retention time and MS In addition, there is also evidence that oligosaccharide multi-esters exhibit anti-dementia, neuroprotective, and antidepressant properties in the literature [37,38]; Saponins not only have anti-HIV effects, but are also the main pharmacological substances that exert tranquilizing, expectorant and cough-relieving effects [39][40][41]; Flavonoid carbon glycosides have antihypertensive, antithrombotic, antitumor, and antiviral properties [42,43]; And organic acids are associated with anti-inflammatory, immunomodulatory, analgesic, and antitumor properties [44]. It is suggested that a variety of components in NLP work together to strengthen the brain and soothe the nerves, protect the nervous system, and regulate immunity.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanistic studies have shown that herbal medicines used for the treatment of depression, anxiety, and insomnia may exert their effect through various mechanisms of action. Components of ginseng (Withania somnifera L.), Ginkgo biloba L., and St John's Wort (Hypericum perforatum L.) have been shown to influence the reuptake of neurotransmitters, such as norepinephrine, dopamine, and serotonin [70,89,90]. Extracts of jujube seeds and valerian (Valeriana officinalis L.) directly interact with serotonin receptors [64,89], and Griffonia simplicifolia Baill.…”
Section: Discussionmentioning
confidence: 99%
“…have been shown to promote GABA release in mouse brain slices [85]. Tenufolin, the active component of Polygala tenuifolia, increases the expression of GABA transporter 1 and GABA availability in animal models [70,71]. Activation of GABA synthesis through enhanced expression of glutamic acid decarboxylase (GAD) has been demonstrated for sanjoinine A, an alkaloid isolated from jujube (Zizyphus jujuba) [63].…”
Section: Other Mechanisms Of Action Related To Gaba Signalingmentioning
confidence: 99%